Hierarchical sensory processing in zebrafish thalamocortical-like circuits - Anh-Tuan Trinh; Anna Maria Ostenrath; Ignacio del Castillo-Berges; Fanchon Cachin; Mina Koç; Susanne Kraus; Bram Serneels; Koichi Kawakami; Emre Yaksi (Science, 2026)
Thalamocortical projections shape the functional regionalization and parallel sensory computations across the mammalian cortex. However, the principles of thalamocortical computations in non-mammalian vertebrates remain underexplored. Here we investigated how the zebrafish pallium, a homolog of the vertebrate cortex, receives and processes sensory information, and how its architecture compares to thalamocortical circuits in other vertebrates. We revealed that the preglomerular complex (PG), a thalamocortical-like pathway, is the primary source of visual and vibrational information to the zebrafish pallium. PG and its pallial projections exhibit sensory-specific and topographically organized responses. In contrast, pallial neurons display topographically organized hierarchies, ranging from sensory-specific to multimodal and coincidence-detecting nonlinear responses. Our results suggest that hierarchies of sensory transformations across topographically organized thalamocortical-like circuits reflect a convergent principle across vertebrates.